EDUCATING ASYLUM SEEKERS AND REFUGEES TO COPE WITH POST-TRAUMATIC STRESS: AN ETHNIC APPROACH TO PROFESSIONAL AND LAY INTERVENTIONS - Salem, Ingrid; Renner, Walter (European Scientific Journal, ESJ, 2015)
According to the United Nations High Commissioner for Refugees (UNHCR), in January 2015 there were 622,384 asylum seekers or refugees from Syria living in Jordan. According to the same source, there are intense endeavors by private and public agencies aiming at improving their living conditions especially from an educational perspective. Focusing on this current challenge to Jordan, we present suggestions to deal with posttraumatic symptomatology in refugees in a culturally sensitive way in order to educate clients towards effective coping with their symptoms. First, we present experiences from a qualitative study on ethnic interventions at the Waiern Clinic in Austria for refugees from former Yugoslavia. Preliminary results have been highly encouraging, as participants reported to have benefitted especially from the culturally sensitive aspects of the interventions. Second, we report about a randomized, controlled study from Austria (total sample of N = 94), which examined the effects of self-help groups for asylum seekers and refugees from Chechnya. In the course of 15 sessions of guided self-help groups, we found statistically significant and large effects with respect to the reduction of clinical symptoms as compared to the Wait-List Control Group in traumatized participants. These effects remained stable over a six-month follow-up period. From the results it is concluded that ethnic interventions can be highly beneficial for asylum seekers and refugees towards educating them in dealing with post-traumatic symptomatology. The findings could instigate additional endeavors to assist Syrian refugees and might be of interest for psychiatrists, clinical psychologists, social workers, and policy makers.